2015
DOI: 10.1095/biolreprod.115.131326
|View full text |Cite
|
Sign up to set email alerts
|

L-Carnitine and Pyruvate Are Prosurvival Factors During the Storage of Stallion Spermatozoa at Room Temperature1

Abstract: The spermatozoa of many stallions do not tolerate being cooled, restricting the commercial viability of these animals and necessitating the development of a chemically defined room temperature (RT) storage medium. This study examined the impact of two major modulators of oxidative phosphorylation, pyruvate (Pyr) and L-carnitine (L-C), on the storage of stallion spermatozoa at RT. Optimal concentrations of Pyr (10 mM) and L-C (50 mM) were first identified and these concentrations were then used to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
83
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(92 citation statements)
references
References 53 publications
7
83
1
1
Order By: Relevance
“…In the present study, we found that DNA fragmentation level was significantly reduced in the semen samples, when these were cryopreserved with LC. Our findings of the protective effect of LC against DNA damage are in agreement with studies by Zhang et al [26] and Gibb et al [30]. In contrast, Manee-In et al [28] and Banihani et al [22, 23] observed no effect of LC on sperm DNA integrity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, we found that DNA fragmentation level was significantly reduced in the semen samples, when these were cryopreserved with LC. Our findings of the protective effect of LC against DNA damage are in agreement with studies by Zhang et al [26] and Gibb et al [30]. In contrast, Manee-In et al [28] and Banihani et al [22, 23] observed no effect of LC on sperm DNA integrity.…”
Section: Discussionsupporting
confidence: 93%
“…As shown in Table 2, none of the tested antioxidants significantly improved chicken spermatozoal acrosome status, similarly as in the studies on mammals [28, 30, 41, 43, 46]. Previously, we obtained comparable results with other antioxidants in the chicken semen [36].…”
Section: Discussionsupporting
confidence: 79%
“…A recent study in stallion sperm incubated in a modified BWW with 10 mM pyruvate concentration demonstrated an increase in motility but also an increase in ROS, suggesting a metabolic role of the pyruvate supplementation [46]. We have demonstrated the mechanism by which pyruvate supplementation leads to increased ROS through mitochondrial leakage due to intense mitochondrial activity.…”
Section: Ros Can Be Both Pathologic and A Biomarker Of Intense Mitochsupporting
confidence: 54%
“…The impact of lipid peroxidation on sperm function is clearly reflected by the loss of motility observed following cryopreservation/thaw‐out. Indeed, the relationship between lipid peroxidation and motility is evident when mammalian spermatozoa are more likely to retain their function when exposed to antioxidants, such as melatonin, genistein, carnitine, or α‐tocopherol, during cryostorage (Ashrafi et al, ; Gibb, Lambourne, Quadrelli, Smith, & Aitken, ; Longobardi et al, ; Satorre, Breininger, & Beconi, ; Thomson et al, ).…”
Section: Impact Of Oxidative Stress On Spermatozoamentioning
confidence: 99%